Pengaruh Pendapatan Nasabah Terhadap Tingkat Pengembalian Pembiayaan Murabahah PT. Bank Muamalat Indonesia Tbk Kantor Cabang Binjai - Muhammad Fitra Dana; Anjur Perkasa Alam (Balance : Jurnal Akuntansi dan Manajemen, 2022)
The purpose of this study was to determine the effect of the magnitude of the influence and the relationship between customer income on the rate of return on murabahah financing at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office. The type of research carried out is quantitative research that emphasizes numerical data (numbers) which is processed by inferential statistical methods (performing analysis of relationships between variables by testing hypotheses). The source of this research data was obtained from the answers to the questionnaire given by the research respondents, namely customers who received cheap financing from PT. Bank Muamalat Indonesia. The results of the study explain that there is a significant influence between customer income on the rate of return on murabahah financing at PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office. The income of customers for their business affects the rate of return on murabahah financing provided by PT. Bank Muamalat Indonesia, Tbk Binjai Branch Office to these customers amounted to 89.4%. There is a positive or in line between the Customer's Income (X) and the Rate of Return on Murabahah Financing (Y)